2010
DOI: 10.1016/s0140-6736(09)62067-5
|View full text |Cite
|
Sign up to set email alerts
|

Routine versus clinically driven laboratory monitoring of HIV antiretroviral therapy in Africa (DART): a randomised non-inferiority trial

Abstract: SummaryBackgroundHIV antiretroviral therapy (ART) is often managed without routine laboratory monitoring in Africa; however, the effect of this approach is unknown. This trial investigated whether routine toxicity and efficacy monitoring of HIV-infected patients receiving ART had an important long-term effect on clinical outcomes in Africa.MethodsIn this open, non-inferiority trial in three centres in Uganda and one in Zimbabwe, 3321 symptomatic, ART-naive, HIV-infected adults with CD4 counts less than 200 cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
188
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 245 publications
(200 citation statements)
references
References 14 publications
10
188
2
Order By: Relevance
“…26 The DART trial in Uganda and Zimbabwe compared three-monthly CD4 count monitoring and clinical monitoring and found higher switching rates in the CD4 monitoring arm. 27 Similarly, the ANRS 12110 trial in Cameroon reported that patients in whom VL and CD4 cell counts were measured every 6 months had higher rates of switching than patients assigned to clinical monitoring. 22 In contrast, a trial from Thailand, which compared CD4 monitoring with VL monitoring, found similar rates of switching.…”
Section: Discussionmentioning
confidence: 99%
“…26 The DART trial in Uganda and Zimbabwe compared three-monthly CD4 count monitoring and clinical monitoring and found higher switching rates in the CD4 monitoring arm. 27 Similarly, the ANRS 12110 trial in Cameroon reported that patients in whom VL and CD4 cell counts were measured every 6 months had higher rates of switching than patients assigned to clinical monitoring. 22 In contrast, a trial from Thailand, which compared CD4 monitoring with VL monitoring, found similar rates of switching.…”
Section: Discussionmentioning
confidence: 99%
“…29 Cases were defined according to available patient records and subsequently categorized into the sub-phenotypes previously described.…”
Section: Methodsmentioning
confidence: 99%
“…Although virologic monitoring is the gold standard for ART monitoring, randomized control trials [5, 26, 27] found routine monitoring of CD4 count to perform similar to virologic monitoring in term of prediction of disease progression and mortality. The WHO based the preference of viral load over CD4 count monitoring on the poor accuracy of routine CD4 count monitoring for early detection of treatment failure when using the WHO definition for immunological failure [28].…”
Section: Discussionmentioning
confidence: 99%
“…Clinical trials have shown that viral load monitoring is a more sensitive and early indicator of treatment failure than CD4 monitoring [35]. In the United States [6], monitoring viral load is therefore recommended every 4–8 weeks until viral suppression is achieved and every 3 to 4 months thereafter during the first 2 years of ART.…”
Section: Introductionmentioning
confidence: 99%